Control electronic implementation of active power filter with rectifier boost technique using op-amp UA741CN / Nor Hafizah Abdullah - Abdullah, Nor Hafizah (2010)
This thesis studies on control Electronic Implementation Of Active Power Filter with Rectifier Boost Technique using op_amp UA741CN. It is a technique for series connected harmonic compensation of a single-phase system feeding non-linear load. An active current wave-shaping boost rectifier technique is proposed to mitigate the distortion of the supply current to shape the pulsating nature of into a continuous, sinusoidal and in phase with the supply voltage. A current control loop (CCL) using standard proportional integral was used to implement PFC to correct the pulsating nature of the input current to almost unity power factor form with low total harmonic distortion (THD) level well below the acceptable limit that was defined in the standard of IEEE 519. The UA741CN operational amplifier has used in this CCL circuit in order to meet such specification. The behavior and operation of the proposed filter structure was examined with computer simulation using MATLAB/simulink and verified experimentally.